Critical care nursing made incredibly easy - Cutler, Judith M.; Cutler, Lee R. (Incredibly easy, 2011)
Suitable for nurses entering or needing a refresher in critical care nursing, this book presents the information on more than 100 critical care disorders, with humour, memory joggers, recurring icons to emphasize key points, and numerous quick-scan tables, illustrations, and flow charts